Comparison of Efficacy of Sertaconazole Nitrate Cream 2 Percent vs Clotrimazole 1 Percent for the Treatment of Tinea Pedis - Madhoo; Ghafoor, Rabia; Batool, Hala; Shafi , Sidra; Das, Jamna; Pirya (Indus Journal of Bioscience Research, 2025)
Introduction: Tinea pedis is commonly referred to as athlete’s foot. Tinea pedis is the consequence of superficial fungal infections on the foot skin brought on by dermatophytes. Among the most prevalent fungal infections of the foot worldwide, its frequency is rapidly rising. Topical imidazoles are effective ways for curing tinea pedis since they work well and have minimal side effects. In the study efficacy of topical Sertaconazole was compared with Clotrimazole on the lesions of Tinea pedis. Objective: To compare the Efficacy of Sertaconazole Nitrate Cream 2% Vs. Clotrimazole 1% for the Treatment of Tinea Pedis. Methodology: This randomized controlled trial study was carried out on OPD patients in the Department of Dermatology, Jinnah Postgraduate Medical Center (JPMC) Karachi, Pakistan. Patients of Tinea Pedis who met the selection criteria were enrolled in the study. Participants were randomly allocated in into two groups; patients of Group-A had used topical Sertaconazole 2% and patients in Group-B had used Clotrimazole 1%. Over four weeks, both creams were used topically twice daily. The patients were assessed at the final follow-up using all clinical investigations and a microscopic analysis. The effectiveness of the therapies was defined as a reduction in the overall composite score of at least two points with a negative KOH test following four weeks of therapy and the reporting of no adverse effects. All of the patients’ adverse drugs events were observed. Results: Mean age was 30.39 years, with an SD of 8.56 years. Males represented 48% of patients in the Clotrimazole group and 50% of patients in the Sertaconazole group. Post-treatment signs and symptoms score showed, individuals received Sertaconazole, signs and symptoms reduced significantly. The study finding showed that the efficacy rate of Sertaconazole was higher than the patients in the clotrimazole group (86% vs. 66%; P-value <0.05). Conclusions: Topical sertaconazole 2% cream was found to be highly efficacious and superior to clotrimazole 1% cream in improvement of clinical parameters of tinea pedis.